Latin Literature. (April 2021) - Whitton, Christopher
Abstract : These days Flavian epic and intertextuality go together like toast and butter, or a persistent cough and fever, depending on your taste. Either way, Intertextuality in Flavian Epic. Contemporary Approaches is not perhaps the most startling of titles. But the book within is an impressive collection, its four editors (Neil Coffee, Chris Forstall, Lavinia Galli Milić, and Damien Nelis) leading a star cast of Flavians in a wide-ranging and stimulating set of chapters.